KESEIMBANGAN MENTAL DALAM ERA DIGITAL: DAMPAK MEDIA SOSIAL TERHADAP KESEHATAN PSIKOLOGIS REMAJA - Yusuf Surya Kusuma; Khodijah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a literature study with a qualitative descriptive approach that aims to examine the influence of technology and social media on the development of adolescent behavior. In today's digital era, adolescents are a group that is very connected to cyberspace, making social media a means of self-expression, communication, and the formation of social identity. However, intense use of technology also poses challenges, such as decreased self-control, increased impulsive behavior, and the risk of mental health disorders such as anxiety, stress, and depression. The digital environment plays a significant role in shaping adolescent behavior, both positively and negatively. This study also highlights the phenomenon of alone together and the shift in character values ​​in adolescents, especially in the context of spiritual and social life. To manage the negative impacts and maximize the positive benefits of technology, a holistic approach is needed through digital literacy education, parental guidance, and community involvement in constructive activities. Thus, technology can be used wisely and become a means to support the healthy growth of adolescent character in the big data era.